2005
DOI: 10.1007/s10803-004-1037-3
|View full text |Cite
|
Sign up to set email alerts
|

Goal Directed Locomotion and Balance Control in Autistic Children

Abstract: This article focuses on postural anticipation and multi-joint coordination during locomotion in healthy and autistic children. Three questions were addressed. (1) Are gait parameters modified in autistic children? (2) Is equilibrium control affected in autistic children? (3) Is locomotion adjusted to the experimenter-imposed goal? Six healthy children and nine autistic children were instructed to walk to a location (a child-sized playhouse) inside the psychomotor room of the pedopsychiatric centre located appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 39 publications
5
81
2
5
Order By: Relevance
“…Allen and Courchesne [13], using functional Magnetic Resonance, found that certain areas of the cerebellar vermis are incompletely developed in children with autism. Other studies have stressed the importance of the dopaminergic system and of the basal ganglia [14][15][16]. This also supports the view that movement disorders might play a role in ASD.…”
Section: Motor Developmental Milestones and Asdsupporting
confidence: 71%
“…Allen and Courchesne [13], using functional Magnetic Resonance, found that certain areas of the cerebellar vermis are incompletely developed in children with autism. Other studies have stressed the importance of the dopaminergic system and of the basal ganglia [14][15][16]. This also supports the view that movement disorders might play a role in ASD.…”
Section: Motor Developmental Milestones and Asdsupporting
confidence: 71%
“…Indeed, some authors have speculated that movement disturbances may be directly related to the core symptoms of ASD (e.g., Leary & Hill, 1996). For example, in older children, clumsiness (e.g., Jones & Prior, 1985), difficulty with tasks involving coordinated sequences of movements (e.g., Vernazza-Martin et al, 2005;Wing, 1969), gait abnormalities (e.g., shorter steps, slower pace, unusual arm positions; Damasio & Maurer, 1978;Teitelbaum, Teitelbaum, Nye, Fryman, & Maurer, 1998;Vilensky, Damasio, & Maurer, 1981), and reduced postural stability (Minshew, Sung, Jones, & Furman, 2004) have been reported. Other investigators have indicated that children with ASD perform worse than typically developing children of the same chronological age and like children with developmental delays and younger, mental-age-matched typically developing children on standardized measures of motor skill (Hauck & Dewey, 2001;Manjiviona & Prior, 1995).…”
Section: Movement and Postural Disorders In Young Children With Asdmentioning
confidence: 99%
“…The American Journal of Occupational Therapypoor goal-oriented movement planning (Vernazza-Martin et al, 2005). A recent meta-analysis of motor behavior in 41 studies showed a large effect indicating deficits in motor function in ASD when compared with non-ASD groups at ages ranging from toddlers to adults (Fournier, Hass, Naik, Lodha, & Cauraugh, 2010).…”
mentioning
confidence: 99%